Impact of Communicating With Doctors Via Social Media on Consumers' E-Health Literacy and Healthy Behaviors in China - Tailai Wu PhD; Zhifei He PhD; Donglan Zhang PhD (SAGE Publishing, 2020)
This study investigated the relationship between consumers' communication with doctors and their e-Health literacy and healthy behaviors based on the theory of reasoned action. Five communication activities were identified: following doctors' social media accounts, reading doctors' posts, responding to doctors' posts, favoring (clicking "like" of) doctors' posts, and recommending doctors to other patients. E-Health literacy and healthy behaviors were measured based on instruments used in previous literature. Survey method was used to collect data and a hierarchical regression analysis was used to analyze the relationship between communication activities and consumers' e-Health literacy and healthy behaviors. We found that following doctors' accounts ( r  = 0.127, P  < .001), responding to doctors' posts ( r  = 0.141, P  < .001) and recommending doctors to others ( r  = 0.133, P  < .001) were significantly associated with e-Health literacy, while following doctors' accounts ( r  = 0.091, P  < .001), responding to doctors' post ( r  = 0.072, P  < .01), favoring doctors' posts ( r  = 0.129, P  < .001), and recommending doctors to others ( r  = 0.220, P  < .001) were significantly associated with healthy behaviors. Our study demonstrated that the social network communication between doctors and consumers could be cost-effective in improving intermediary consumers' health outcomes. To be specific, following doctors' posts, responding to doctors' posts, favoring doctors' posts, and recommending doctors to others were positively associated with consumers' e-Health literacy and healthy behaviors. The results suggested that leveraging information technology could be an important tool to health policymakers and health providers in order to improve outcomes.